Evaluation, diagnosis, and treatment of chronic exertional compartment syndrome: a review of current literature - Vajapey, S.; Miller, T. L. (The Physician and Sportsmedicine, 2017)
Chronic exertional compartment syndrome (CECS) is a rare condition that usually affects distance runners and other running athletes. It is characterized by pain and pressure in one or multiple muscle compartments with repetitive physical activity. Reduction in pain typically occurs with cessation of activity. Evaluation of CECS consists of a thorough history of patient symptoms and ruling out of other causes of symptoms. Post-exercise pressure measurements can help confirm the diagnosis when symptoms are consistent and imaging evaluation negative for other causes. Non-operative treatment is a viable option for hindfoot runners and patients with anterior compartment syndrome of the leg. Limited-incision fasciotomy has been shown to be the most effective treatment and remains the gold standard for treatment. Minimal-incision open fasciotomy and endoscopic fasciotomy have surgical outcomes similar to wide-open fasciotomy. Military patients treated with fasciotomy have higher failure rates compared to civilians. Pediatric patients have similar outcomes compared to adults.